Humoral and Cellular Immunogenicity and Safety of Five Different SARS-CoV-2 Vaccines in Patients With Autoimmune Rheumatic and Musculoskeletal Diseases in Remission or With Low Disease Activity and in Healthy Controls: A Single Center Study - Szebeni, Gábor J.; Gémes, Nikolett; Honfi, Dániel; Szabó, Enikő; Neuperger, Patrícia; Balog, József Á.; Nagy, Lajos I.; Szekanecz, Zoltán; Puskás, László G.; Toldi, Gergely; Balog, Attila (Frontiers in Immunology, 2022)
Background Vaccine-induced immunity is essential for controlling the COVID-19 pandemic. Data on humoral and cellular immunogenicity and safety of different SARS-CoV-2 vaccines in patients with autoimmune rheumatic and musculoskeletal diseases (RMDs) are limited. Methods A single centre observational study evaluated the immunogenicity and safety of the two-dose regimen of the BBIBP-CorV inactivated, Gam-COVID-Vac and AZD1222 adenovirus-based, and BNT162b2 and mRNA-1273 mRNA-based vaccines in patients with RMDs (n=89) compared with healthy controls (n=74). Neutralizing anti-RBD (receptor binding domain) specific antibodies and SARS-CoV-2 specific T-cell response were measured one and four months after the second vaccine dose in parallel with vaccination efficacy and safety. Results Disease-specific comparison showed that antibody response at four months was higher in spondylarthropathies compared to rheumatoid arthritis and autoimmune RMDs. Risk factors for reduced immunogenicity included longer disease duration, positive immunoserological profile and anti-CD20 therapy of patients. The rate of positive anti-RBD antibody response for healthy controls versus patients after 4 months post vaccination was 69% vs. 55% for the inactivated viral vaccine BBIBP-CorV, 97% vs. 53% for the pooled data of adenovirus vector-based vaccines Gam-COVID-Vac and AZD1222, or 100% vs. 81% for the pooled data of mRNA vaccines BNT162b2 and mRNA-1273, respectively. Patients who received the inactivated viral vaccine had a lower proportion of TNF-α producing CD4+ T-cells upon SARS-CoV-2 antigen stimulation compared to healthy controls. Conclusion All five investigated vaccines were immunogenic in the majority of patients and healthy controls with variable antibody and T-cell response and an acceptable safety profile.